Budgetary Tools of Public Management of the Reconstruction and Restoration Processes in Local Communities of Ukraine - Zubenko, Vyacheslav (Theory and Practice of Public Administration, 2023)
The article clarifies the essence and systematizes the principles of reconstruction and recovery processes in communities, substantiates the role of budgetary instruments in the public administration of these processes at the local level in Ukraine in war conditions and considering the prospects of post-war recovery.The main principles of reconstruction and recovery in Ukraine are considered, including the immediate start and gradual escalation of the process, increasing well-being based on the principles of justice, integration into the European Union, orientation to the process of better reconstruction for the future, stimulation of private investments, focus on reforms, transparency, accountability and rule of law, democratic participation and multi-stakeholder engagement, gender equality and sustainable development, etc.The main spheres of reconstruction and restoration in Ukrainian communities include both economic and social spheres, including reconstruction of infrastructure, housing stock, security and demining, social support, support of local enterprises, creation of new jobs, stimulation of economic development, etc.The role of the budget in the processes of reconstruction and recovery in communities was studied not only as a source of financing, but also considering its administrative potential. Along with the instruments of direct financing of reconstruction projects from the state and local budgets (local budgets, reserve fund, subventions, recovery funds, assistance of international partners), the importance of the administrative and organizational potential of the budget has been proven. It has been proven that the program-target budget is an important tool for public administration of reconstruction and recovery processes, as it provides strategic planning, targeted financing, prioritization of measures, determination of results, cost effectiveness, monitoring and evaluation, transparency and openness, public involvement.Considering the significant potential of the budget as an administrative tool, the direction of further research is determined by the theoretical justification of the essence, structure, goals, and objectives of the complex financial and budgetary mechanism of public administration of reconstruction and restoration processes in communities.